Cohort profile: the LHIV-Manitoba clinical cohort of people living with HIV in Manitoba, Canada. Issue 5 (27th May 2020) - McClarty, Leigh M; Cheuk, Eve; Ireland, Laurie; Kendall, Claire; Bibeau, Christine; Loeppky, Carla; Kasper, Ken; Keynan, Yoav; Blanchard, James; Becker, Marissa
Abstract : Purpose: The LHIV-Manitoba cohort was developed as a way to provide a comprehensive source of HIV-related health information in the central Canadian Prairie province of Manitoba. The cohort will provide important information as we aim to better understand local HIV epidemiology and address key knowledge and practice gaps in HIV prevention, treatment and care programming in the province. Participants: In total, 890 individuals, aged 18 or older and living or receiving HIV care in Manitoba are enrolled in the cohort. A complete clinical dataset exists for 725 participants, which includes variables on sociodemographic characteristics, comorbidities and co-infections, self-reported HIV exposure categories and HIV clinical indicators. A limited clinical dataset exists for an additional 165 individuals who were enrolled posthumously. 97.5% of cohort participants' clinical records are linked to provincial administrative health datasets. Findings to date: The average age of cohort participants is 49.7 years. Approximately three-quarters of participants are male, 42% self-identified as white and 42% as Indigenous. The majority of participants (64%) reported condomless vaginal sex as a risk exposure for HIV. Nearly one-fifth (18%) of participants have an active hepatitis C virus infection and the cohort's median CD4 count increased from 316 cells/mm 3 to 518 cells/mm 3 between time of entry into care and end of the first quarter in 2019. Future plans: The LHIV-Manitoba cohort is an open cohort, and as such, participant enrolment, data collection and analyses will be continually ongoing. Future analyses will focus on the impact of provincial drug plans on clinical outcomes, determinants of mortality among cohort participants and deriving estimates for a local HIV care cascade.